An Investigation into the Ethics from the Viewpoint of Erich Fromm With a Focus on the Views of Āyatullāh Jawādī Àmulī - RÙhullÁh ShÁkeri ZavÁrdihi; MuzhgÁn FaghfÙri (حکمت اسرا)
All ethical systems, in accordance with theoretical fundamentals are based upon their own ideological perspectives. This article deals with the issue that Erich Fromm (b. 1900-1980) in formulating his didactic system, has derived humanistic teachings. Thus its ethical propositions are specific to the worldly life of human being and the ethical consequences resulting from this system also fit in with a humanistic society. Since the promotion of humanistic ethics, in addition to turning people away from the true ethical sources of Islam, causes the appearance of atheistic and deviating thoughts in the feilds of ethics and mysticism, the examination of the intellectual bases of this renowned author, particularly with regard to the true Islamic teachings, appears to be useful. Because of a considerably wide range of the issues of the Islamic ethics, the ethical perspectives of Āyatullāh Jawādī Àmulī, which are based on the words of the God Almighty and the conduct of the infallible Imams, have been emphasized in this article directing at criticizing the views of Erich Fromm. Āyatullāh Jawādī Àmulī has stressed the spiritual and bodily aspects of human existence as well as the immortality of his spiritual dimention; thus, he thinks that the observance and practice of the ethical Islamic teachings, is effective not only in the present life, but also in the eternal and other-worldly life. The present study deals with the distinction of the fundamentals of the ethical views of Erich Fromm with the ethical perspectives of Islam in the way of formulation of the principles for the attainment of happiness.